2014
DOI: 10.1038/nrmicro3274
|View full text |Cite
|
Sign up to set email alerts
|

Motility and more: the flagellum of Trypanosoma brucei

Abstract: A central feature of trypanosome cell biology and life cycle is the parasite’s single flagellum, which is an essential and multifunctional organelle involved in cell propulsion, morphogenesis and cytokinesis. The flagellar membrane is also a specialized subdomain of the cell surface that harbors multiple parasite virulence factors with roles in signaling and host-parasite interactions. In this review, we discuss the structure, assembly and function of the trypanosome flagellum, including canonical roles in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
158
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(180 citation statements)
references
References 173 publications
5
158
0
2
Order By: Relevance
“…As the daughter cells move apart, they become oriented such that beating of the extracellular flagella can propel the cells in opposite directions for scission. A mechanical role for the flagella, however, does not exclude the possibility that the flagella could have additional roles, such as serving as a scaffold for transport or polarity signaling (51,60,61).…”
Section: Giardia Uses a Tubulin Reservoir To Support Rapid Mitosis Anmentioning
confidence: 99%
See 1 more Smart Citation
“…As the daughter cells move apart, they become oriented such that beating of the extracellular flagella can propel the cells in opposite directions for scission. A mechanical role for the flagella, however, does not exclude the possibility that the flagella could have additional roles, such as serving as a scaffold for transport or polarity signaling (51,60,61).…”
Section: Giardia Uses a Tubulin Reservoir To Support Rapid Mitosis Anmentioning
confidence: 99%
“…Myosin II mutants of Dictyostelium were shown to use ameboid motility to crawl apart for cytokinesis (17). Organisms that lack myosin II and depend on their flagella for motility, such as Trypanosoma brucei and Tetrahymena, also require motility for abscission (50)(51)(52). To address whether the flagella have a direct role in cytokinesis, we treated Giardia with small molecule inhibitors that have been shown to disrupt flagellar function in other systems [Ciliobrevin A, Ciliobrevin D, drug E, drug F, and drug P (53-55)].…”
Section: Giardia Uses a Tubulin Reservoir To Support Rapid Mitosis Anmentioning
confidence: 99%
“…Given the multiple important roles that flagella play for trypanosomes, these cellular appendages have been studied extensively (3,4). Although studies on axonemal and luminal proteins predominated originally, considerable work has been done more recently on proteins of the trypanosome flagellar membrane (5).…”
mentioning
confidence: 99%
“…These parasites are flagellated in all life cycle stages, including the bloodstream forms (BFs) 4 that infect the mammalian host and in all of the developmental stages that infect the tsetse fly vector. Given the multiple important roles that flagella play for trypanosomes, these cellular appendages have been studied extensively (3,4).…”
mentioning
confidence: 99%
“…Notably, several flagellar ACs were recently identified that are specifically upregulated in procyclic T. brucei (25), the parasite life cycle stage that undergoes social motility. Given the widespread use of cyclic nucleotides in control of microbial social behavior and the emerging role of the eukaryotic flagellum in coordinating cellular responses to external signals (28,29), we asked whether T. brucei flagellar ACs function in social motility. Here we report that AC6, a procyclic stage-specific AC (25), is localized to the tip of the flagellum and regulates social motility.…”
mentioning
confidence: 99%